2014
DOI: 10.1055/s-0034-1382839
|View full text |Cite
|
Sign up to set email alerts
|

Monoterpenoid Coumarins from the Peels of Clausena lansium

Abstract: A phytochemical investigation on the peels of Clausena lansium (Lour.) Skeels led to the isolation of two new monoterpenoid coumarins, named clauslactone V (1) and clauslactone W (2), together with three known analogues (3-5). Their structures were elucidated by spectroscopic techniques (UV, IR, MS, 1D and 2D NMR). All the compounds were evaluated for hypoglycemic activity, and compounds 1-5 showed α-glucosidase inhibitory activity in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 15 publications
(24 reference statements)
0
12
0
Order By: Relevance
“…2) all have the same physical state as a colorless oil with a blue fluorescence under the ultraviolet lamp (254 nm), so, they are the same series of compounds with a similar furanocoumarin skeleton. Comparing the experimental data of compounds 3-9 with those described in the literature, their phytochemical structures were identified as: wampetin (3), 17 anisolactone (4), 14,15 11 lansiumarin A (6), 20 8-[(2E)-6-oxo-3,7-dimethyloct-2-enyloxy] psoralen (7), 21 (S,E,E)-8-[(6-hydroxy-3,7-dimethylocta-2,7-dien-1-yl)oxy]-psoralen (8) 11 and 8-geranyloxypsolaren (9). 22 Compounds 10-15 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2) all have the same physical state as a colorless oil with a blue fluorescence under the ultraviolet lamp (254 nm), so, they are the same series of compounds with a similar furanocoumarin skeleton. Comparing the experimental data of compounds 3-9 with those described in the literature, their phytochemical structures were identified as: wampetin (3), 17 anisolactone (4), 14,15 11 lansiumarin A (6), 20 8-[(2E)-6-oxo-3,7-dimethyloct-2-enyloxy] psoralen (7), 21 (S,E,E)-8-[(6-hydroxy-3,7-dimethylocta-2,7-dien-1-yl)oxy]-psoralen (8) 11 and 8-geranyloxypsolaren (9). 22 Compounds 10-15 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Further analysis of the carbon‐13 ( 13 C)‐NMR spectrum (Table 1) of compound 1 suggested a furanocoumarin system and an additional C 10 side‐chain moiety with one methoxy ( δ C 61.4), which consisted of one ester carbonyl ( δ C 173.7), two vinyl methyl groups ( δ C 16.9, 10.7), one oxymethine ( δ C 77.9), oxy methylene ( δ C 71.7), one methylene ( δ C 43.0), and two trisubstituted double bonds ( δ C , 147.9, 148.2, 130.4, 119.8), respectively. Detailed comparison of the 1 H‐ and 13 C‐NMR data and the MS (ESI‐MS m/z : 419 [M + Na] + ) of compound 1 and anisolactone 14–17 indicated them to be similar O ‐monoterpenoid furanocoumarins, differing only in the presence of a more methoxy ( δ H 3.38, δ C 61.4) in compound 1 than in anisolactone. In the heteronuclear multiple‐bond correlation (HMBC) experiment of compound 1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some monoterpenoid coumarins and seven carbazole alkaloids were also isolated from the peels of Clausena lansium (Lour.) Skeels, and claulansine J exhibited moderate antibacterial activity against Staphylococcus aureus [ 39 , 40 ]. Three new jasmonoid glucosides, two new sesquiterpenes, two new coumarins, and others were isolated from the fruit of C. lansium .…”
Section: Resultsmentioning
confidence: 99%
“…C. lansium is famous for their fruits, which are usually very popular tropical, health-promoting fruits, while their roots, stems, leaves, and seeds have also been extensively applied in folk medicine or traditional Chinese medicine for the treatments of abdominal pain, malaria, cold, dermatopathy, and snake bites [2,3]. Various biological studies, on the alkaloids, coumarins, and sesquiterpenes from this plant have reported the neuroprotective [4,5], antitumor [6,7], hepatoprotective [8], anti-inflammatory [9], antifungal [10], antioxidant [11], antiobesity [12], nematicidal [13], antimicrobial [14], and hypoglycemic [15] effects of the C. lansium . In our previous studies, some carbazole alkaloids [16] and coumarins [17] were separated from the stem and leaf of C. lansium .…”
Section: Introductionmentioning
confidence: 99%